Brown fat triglyceride content is associated with cardiovascular risk markers in adults from a tropical region - Monfort-Pires, Milena; Regeni-Silva, Giulianna; Dadson, Prince; Nogueira, Guilherme A.; U-Din, Mueez; Ferreira, Sandra R. G.; Sapienza, Marcelo Tatit; Virtanen, Kirsi A.; Velloso, Licio A. (Frontiers in Endocrinology, 2022)
Brown adipose tissue (BAT) is regarded as an interesting potential target for the treatment of obesity, diabetes, and cardiovascular diseases, and the detailed characterization of its structural and functional phenotype could enable an advance in these fields. Most studies evaluating BAT structure and function were performed in temperate climate regions, and we are yet to know how these findings apply to the 40% of the world’s population living in tropical areas. Here, we used 18F-fluorodeoxyglucose positron emission tomography – magnetic resonance imaging to evaluate BAT in 45 lean, overweight, and obese volunteers living in a tropical area in Southeast Brazil. We show that BAT glucose uptake is not correlated with leanness; instead, BAT triglyceride content is correlated with visceral adiposity and markers of cardiovascular risk. This study expands knowledge regarding the structure and function of BAT in people living in tropical areas. In addition, we provide evidence that BAT triglyceride content could be an interesting marker of cardiovascular risk.